SINTESIS ALKIL N-ASETILGLUKOSAMINA (ALKIL-GLCNAC) DENGAN ENZIM N-ASETILHEKSOSAMINIDASE YANG DIISOLASI DARI ASPERGILLUS SP. 501 - Saskiawan, Iwan; Handayani, Rini (JURNAL BIOLOGI INDONESIA, 2011)
ABSTRACTEnzymatic Synthesis of Alkyl N-acetylglucosamine (Alkyl-GlcNAc) by Application ofTransglycosylation Activity of ?-N-Acetylhexosaminidase from Aspergillus sp. 501. ?-NAcetylhexosaminidasefrom Aspergillus sp. 501 has transglycosylation and hydrolytic activity.Transglycosylation occur through transfer of N-acetylglucosamine (GlcNAc) which washydrolyzed from p-nitrophenyl-?-N-acetylglucosamine (pNP-GlcNAc) to various alcohols. Thetransglycosylation product was determined by Thin Layer Chromatography and HighPerformance Liquid Chromatography. Using this transglycosylation activity the novelcompound of Alkyl-GlcNAc was synthesized using N-acetylchitotriose as a donor and anethanol as an acceptor.Keywords: Alkyl N-acetylglucosamine, Transglycosylation, ?-N-Acetylhexosaminidase,Aspergillus sp. 501